The Effect of Test Techniques on the Students’ Reading Achievement - Rusmawati, Adi (ENGLISH JOURNAL, 2016)
Many argue that either multiple choice items or short-answer questions have their own strength and weaknesses. However the research of identifying the effect of both test techniques on certain language skills, particularly reading, is still limited. Therefore, this study is important to be conducted. Specifically, the objectives of this study were 1) to identify the reading achievement of the students who were assessed English reading using multiple choice items format, 2) to identify the reading achievement of the students who were assessed English reading using short-answer items format and 3) to know whether there was a significant difference between students’ reading achievement who were assessed English reading using multiple choice items format and those who were assessed English reading using short-answer items format. This study utilized a true experimental design with a purposive sampling assignment involving twenty respondents for experiment group and the same number of respondents for control group. The respondents of experiment group consisting of students whose their reading achievement was assessed using multiple choice items (determined as variable x) while the respondents of control group comprised students whose their reading achievement was assessed using short-answer items (determined as variable y). The instruments used were taken from reading section for the TOEFL. The data were then analyzed quantitatively. The result indicated that the students’ reading achievement who were assessed using multiple choice item was much better than those who were assessed using short-answer item. It was seen from the mean score of variable x (7.03) which was higher that variable y (4.6). This difference was proven to be quite significant after seeing at the t-counted (3.74) which was higher than the t-table (1.68).